Communication Styles Between Seller And Buyer In Online Transactions On Facebook Marketplace (A Case Study On Zidan Lesmana's Account) - Yahya , Jorgi; Narti, Sri; Dianthi, Martha Heriniazwi (Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the communication styles used by sellers and buyers during online transactions on Facebook Marketplace, focusing on the seller account named Zidan Lesmana. The research background is based on the growing trend of online buying and selling activities that rely heavily on digital communication, where communication styles play a crucial role in building trust and influencing purchase decisions. This research employs a descriptive qualitative approach and a case study method. Data collection techniques include participatory observation, in-depth interviews, and documentation. The study is grounded in Norton’s (1983) communication style theory, which classifies communication into nine types. The findings show that Zidan Lesmana applies various adaptive communication styles, including dominant, dramatic, contentious, animated, impression-leaving, relaxed, attentive, open, and friendly. The relaxed and attentive styles are dominant in maintaining a comfortable interaction, while the dramatic and animated styles are used to attract attention and foster emotional closeness. Open and attentive styles help build trust, while the impression-leaving style enhances the seller’s image in the long run. The study concludes that successful transactional communication on Facebook Marketplace depends not only on product information but also on the appropriate interpersonal communication strategies within digital contexts.